Transient colonization by Priestia megaterium B1L5 alters the structure of the rhizosphere microbiome towards potential plant beneficial bacterial groups in apple plantlets - Fatma M. Mahmoud; Holger Edelmann; Yang Si; Lea Endrejat; Karin Pritsch; Caroline Gutjahr; Armin Ehrenreich; Traud Winkelmann; Jana Barbro Winkler; Jörg‑Peter Schnitzler; Michael Schloter (Environmental Microbiome)
Abstract Background Plant growth-promoting bacteria (PGPB) can beneficially modulate rhizosphere microbial communities, potentially improving plant health and reducing disease incidence. Limited research exists on the influence of PGPB inoculation on the rhizosphere microbial communities of apple plants, particularly in soils affected by apple replant disease (ARD). Here, we evaluated the capacity of GFP-labelled Priestia megaterium B1 (designated as P. megaterium B1L5) to colonize the roots of apple plantlets grown in two soils: ARD-affected soil and ARD-unaffected grass soil. We investigated its influence on plant growth in ARD-affected soil and its potential to mitigate ARD-related symptoms. We also assessed how its inoculation modulates the rhizosphere microbial communities, with emphasis on changes that may support plant health, particularly in ARD-affected soils. Results P. megaterium B1L5 successfully colonized apple roots in both soils 6 days post-inoculation (dpi), but was not detectable at 33 dpi. In ARD-affected soil, plants inoculated with vegetative cells or spores displayed a lower proportion of blackened root tips compared to uninoculated controls. Beta diversity and PERMANOVA analyses demonstrated a significant influence of inoculation on the bacterial communities in both soils at 6 and 33 dpi (p = 0.001). Furthermore, inoculation enriched the rhizosphere of apple plantlets with potential plant-beneficial bacteria, such as Luteimonas, Lysobacter, Pseudomonas, Sphingomonas, Sphingobacterium, Rhodanobacter, Pedobacter and Flavobacterium. In contrast, fungal communities remained largely unaffected by inoculation. Most bacterial and fungal shifts observed in the rhizosphere of inoculated plantlets at 33 dpi did not exhibit similar patterns in uninoculated controls over time, indicating that these shifts were largely driven by the inoculum rather than by plant development or natural microbial succession. Conclusions Our results highlight the capacity of P. megaterium B1L5’s to transiently colonize apple plant roots across different soil environments. The observed tendency toward reduced root tip blackening in inoculated plants grown in ARD-affected plants reflects its potential for alleviating stress associated with ARD. Additionally, inoculation with P. megaterium B1L5 promoted beneficial shifts in the rhizosphere microbiome by enriching bacterial taxa commonly linked to plant health. These findings indicate that P. megaterium B1L5 presents a candidate for ARD mitigation, however its long-term efficacy and practical application should be further evaluated.